FINANCIAL REPORT QUALITY, ACCOUNTING INFORMATION SYSTEMS, INTERNAL CONTROL SYSTEMS, AND LABOR EFFICIENCY'S EFFECT ON MANAGERIAL PERFORMANCE AT PT. KAHATEX - Eltie Christi Sandag; Ribka Sari Butar-butar; Ibnu Sutomo; Arifia Nurriqli (International Journal of Economics and Management Research, 2023)
This research was conducted at PT. Kahatex. The purpose of this study is to analyze the effect of the quality of financial reports, the role of accounting information systems, internal control systems, and workforce efficiency on the managerial performance of PT. Kahatex. The population and sample in this study are 45 financial employees of PT. Kahatex. The sampling technique used is a census sampling. The data collection techniques used are questionnaires, interviews, and documentation studies. The type of data used is quantitative data. Data analysis uses multiple linear regression analysis. The conclusion of the study is that simultaneously and partially, the quality of financial reports, the role of accounting information systems, internal control systems, and workforce efficiency have a positive and significant effect on the managerial performance of PT. Kahatex.